Endovascular treatment of pediatric ruptured intracranial dissecting aneurysm: a case report and literature review - Xu, Haitong; Qin, Yongkai; Zhang, Liyang; Chen, Jiahong; Li, Bo; Han, Junfei; Huang, Zhengwei; Jing, Yingchao (Frontiers in Surgery, 2026)
Intracranial aneurysms (IAs) are uncommon in children, with an incidence of 1%–5%. However, intracranial dissecting aneurysms (IDA) account for a higher proportion (20%–50%) of all aneurysms in this age group. Pediatric IDAs typically result from vascular wall injury, potentially associated with genetic predisposition, congenital defects, or trauma. These lesions most commonly present with ischemic stroke, while subarachnoid hemorrhage (SAH) is relatively rare. Early symptoms include headache and vomiting, with severe cases potentially leading to neurological deficits. Digital subtraction angiography (DSA) remains the gold standard for diagnosis. Timely diagnosis and intervention are critical for improving prognosis. Treatment options include pharmacological therapy, endovascular intervention, and microsurgical repair. This report details a case of a 14-year-old male diagnosed with a dissecting aneurysm in the communicating segment of the left internal carotid artery (ICA). Emergency endovascular intervention with coil occlusion of the parent artery was performed. Short-term follow-up demonstrated favorable outcomes without new neurological deficits. The clinical characteristics of this condition are briefly reviewed in the context of this case.